2000
DOI: 10.1046/j.1365-8711.2000.03507.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optical polarimetry and X-ray data of the near-synchronous polar RX J2115-5840

Abstract: A B S T R A C TWe present simultaneous optical polarimetry and X-ray data of the near-synchronous polar RX J2115±5840. We model the polarization data using the Stokes imaging technique of Potter et al. We find that the data are best modelled using a relatively high binary inclination and a small angle between the magnetic and spin axes. We find that, for all spin±orbit beat phases, a significant proportion of the accretion flow is directed on to the lower hemisphere of the white dwarf, producing negative circu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 21 publications
5
30
0
Order By: Relevance
“…This variability is best shown in the Ginga data which was taken over 3 days and showed a periodic modulation in the first half which disappeared in the second half and was thereafter dominated by strong flaring. This is consistent with X‐ray observations of one other asynchronous polar RX J2115–58 which showed highly variable light curves (Ramsay et al 2000). This variability was interpreted as the accretion flow rotating around the magnetic field of the white dwarf and at certain instances the flow accretes on to the opposite hemisphere of the white dwarf resulting in a different shaped light curve.…”
Section: Introductionsupporting
confidence: 91%
“…This variability is best shown in the Ginga data which was taken over 3 days and showed a periodic modulation in the first half which disappeared in the second half and was thereafter dominated by strong flaring. This is consistent with X‐ray observations of one other asynchronous polar RX J2115–58 which showed highly variable light curves (Ramsay et al 2000). This variability was interpreted as the accretion flow rotating around the magnetic field of the white dwarf and at certain instances the flow accretes on to the opposite hemisphere of the white dwarf resulting in a different shaped light curve.…”
Section: Introductionsupporting
confidence: 91%
“…It was first discovered in V1500 Cyg in 1988 in the form of ~7 day variations in the average brightness [7], which can be in the shape of a one or two hump wave [8]. Ramsay et al [9] found variations in the circular polarization of RX J2115-5840 with a period of 6.3 days, while Friedrich et al [10] discovered a modulation in the x-ray light curves with the phase of a beat period of 49.5 days. The most vivid manifestation of this period in BY Cam was found during the international "Noah project" [11]: twice the synodic cycle (14.…”
mentioning
confidence: 99%
“…There are four known nearly synchronous Polars: V1500 Cyg (e.g., Schmidt et al 1995), BY Cam (e.g., Mason et al 1998), V1432 Aql (e.g., Geckeler & Staubert 1997), RX J2115À5840 (Ramsay et al 2000), and one candidate, V4633 Sgr (Lipkin et al 2001). Warner (1995) explained that as the primary of the binary system rotates asynchronously, the accretion flow is more variable than for a phase-locked Polar.…”
Section: A Nearly Synchronous Polar?mentioning
confidence: 99%